Implementation of the connected mathematics project learning model on students' mathematical critical thinking ability - Harahap, Sinar Depi; Sabri, Sabri; Ahmad, Marzuki (Jurnal Gantang, 2023)
Students' low critical thinking ability in learning mathematics is a major problem in research. This needs to be overcome by implementing learning that provides opportunities for students to develop their thinking ability rationally and well-structured in learning mathematics. One learning model that supports this learning is the Connected Mathematics Project (CMP) learning model. This study aimed to describe quantitatively the implementation of the CMP learning model on students' critical thinking ability in mathematics. This type of research is quasi-experimental with a one-group pre-test and post-test post-test design. The research instruments were observation sheets and tests. The results showed that the application of learning observed in 4 meetings in terms of 9 student activities in learning in the sample group met the criteria for being effective. The student's critical thinking ability through the paired t-test showed a significance value of 0.00, which was smaller than the alpha level of 0.05, meaning that there was a significant difference in the average score from the pre-test to the post-test. Furthermore, the n-gain value obtained is 0.36 (medium). Thus, it was concluded that implementing CMP learning on students' critical thinking ability was effective.